Улучшение качества процесса разработки программного обеспечения на основе методов последовательного анализа вариантов и локальной оптимизации - Годлевский, Михаил Дмитриевич; Рубин, Э. Е.; Голоскокова, Анна Александровна (НТУ "ХПИ", 2014)
Предлагается совместное использование метода локальной оптимизации и алгоритма последовательного анализа вариантов для улучшения качества процесса разработки программного обеспечения. На основании полученного результата были сделаны выводы, что совместное использование методов обеспечивает уменьшение количества возможных вариантов развития данного процесса разработки.

There have been proposed the interplay of the method of local optimization and the sequential analysis of variants method for quality improvement of the software development process. As far as, with the use of the developed algorithm of the sequential analysis of variants method, total time spent solving this problem is much higher than the permissible limits. The next conclusions have been made based on the results: the methods interplay provides quantity reduction of possible options of the software development process evolution. Also the interplay of the above mentioned methods makes it possible to reduce the complexity of the solving problem, but it does not provide a guarantee, that this solution corresponds to the global extremum.
Quality improvement of the software development process based on the sequential analysis of variants method and the method of local optimization
Keywords: программное обеспечение; локальная оптимизация; последовательный анализ вариантов; процессы жизненного цикла; модель зрелости; local optimization; sequential analysis of variants